Thiourea-Grafted Graphite Felts as Positive Electrode for Vanadium Redox Flow Battery - Wu, Shangzhuo; Lv, Xin; Ge, Zhijun; Wang, Ling; Dai, Lei; He, Zhangxing (Frontiers in Chemistry, 2021)
In this paper, thiourea was successfully grafted onto the surface of acid pre-processed graphite felts (GF) by thiol-carboxylic acid esterification. The thiourea grafted graphite felts (TG-GF) were investigated as the positive electrode for vanadium redox flow battery (VRFB). X-ray photoelectron spectroscopy results suggested that thiourea was grafted into the surface of graphite felts. The cyclic voltammetry showed that the peak potential separation decreased by 0.2 V, and current peaks were greatly enhanced on the TG-GF electrode compared with GF electrode, implying improved electro-catalytic activity and reversibility of the TG-GF electrode toward the VO2+/VO2+ redox reaction. The initial capacity of the TG-GF based cell reached 55.6 mA h at 100 mA cm-2, 22.6 mA h larger than the GF based cell. The voltage efficiency and energy efficiency for the cell increased by 4.9% and 4.4% compared with those of the GF based cell at 100 mA cm-2, respectively.